Acclimation of leaf respiration consistent with optimal photosynthetic capacity. (24th February 2020) - Wang, Han; Atkin, Owen K.; Keenan, Trevor F.; Smith, Nicholas G.; Wright, Ian J.; Bloomfield, Keith J.; Kattge, Jens; Reich, Peter B.; Prentice, I. Colin
Abstract: Plant respiration is an important contributor to the proposed positive global carbon‐cycle feedback to climate change. However, as a major component, leaf mitochondrial ('dark') respiration ( R d ) differs among species adapted to contrasting environments and is known to acclimate to sustained changes in temperature. No accepted theory explains these phenomena or predicts its magnitude. Here we propose that the acclimation of R d follows an optimal behaviour related to the need to maintain long‐term average photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used for photosynthesis. To test this hypothesis, we extend photosynthetic co‐ordination theory to predict the acclimation of R d to growth temperature via a link to V cmax, and compare predictions to a global set of measurements from 112 sites spanning all terrestrial biomes. This extended co‐ordination theory predicts that field‐measured R d and V cmax accessed at growth temperature ( R d, tg and V cmax, tg ) should increase by 3.7% and 5.5% per degree increase in growth temperature. These acclimated responses to growth temperature are less steep than the corresponding instantaneous responses, which increase 8.1% and 9.9% per degree of measurement temperature for R d and V cmax respectively. Data‐fitted responses proof indistinguishable from the values predicted by our theory, and smaller than the instantaneous responses. Theory and data are also shown to agree that the basal rates of both R d and V cmax assessed at 25°C ( R d, 25 and V cmax, 25 ) decline by 4.4% per degree increase in growth temperature. These results provide a parsimonious general theory for R d acclimation to temperature that is simpler—and potentially more reliable—than the plant functional type‐based leaf respiration schemes currently employed in most ecosystem and land‐surface models. Abstract : We propose an optimality‐based theory of leaf dark respiration ( R d ) thermal acclimation by assuming that R d follows the optimal behaviour of photosynthetic capacity ( V cmax ) so that available environmental resources can be most efficiently used. We predict R d and V cmax increase with growth temperature by 3.7% and 5.5% per degree warming. Those theoretical predictions are supported by the global field data, as indicated by the overlapped lines. The acclimated responses are indeed less steep than the instantaneous responses. Our results provide a parsimonious general theory for R d thermal acclimation that is typically missing in Earth System models.